Cryogelation of Human Hair Keratins. Issue 21 (9th August 2020) - Chua, Huei Min; Zhao, Zhitong; Ng, Kee Woei
Abstract: Human hair keratins (HHK) are known for their biocompatibility and potential to regulate cell response, possibly due to the presence of the leucine‐aspartic‐valine cell adhesion and signaling motifs. Together with the abundance of cysteine residues in HHK, 3D HHK scaffolds are fabricated through cryogelation based on spontaneous disulfide crosslinks and noncovalent interactions. Herein, the molecular mechanism of HHK self‐assembly during cryogelation is interrogated and the influence of cryogelation parameters on the properties of the resultant scaffolds is studied. With successive freeze–thaw cycles, the storage modulus ( G ′) of HHK cryogels substantially improves from 116.4 Pa at freeze–thaw cycle 3 (FT3) to 1908.7 Pa at freeze–thaw cycle 10 (FT10). Meanwhile, it is found that complete thiol‐capping of HHK samples significantly inhibits cryogel formation as compared to partially or uncapped HHK samples, suggesting the dominant role of disulfide stabilization in cryogelation. Finally, uniaxial compression tests on HHK sponges demonstrate that FT cycling, from 0 to 10, is able to improve the compression modulus of sponges by ≈12‐folds. These findings show that macroscale properties of HHK cryogels can be conveniently modulated by physical parameters of cryogelation and that disulfide bonding is the main stabilizing force in HHK cryogels. Abstract : Purified human hair keratin intermediate filament proteins crosslink naturally when subjected to successive freeze–thaw cycles (cryogelation) and are able to form 3D porous scaffolds. Modulation of cryogelation parameters such as the freezing and thawing temperature and number of freeze–thaw cycles enables tunable scaffold properties. Combined with the biocompatibility of keratin, these scaffolds can be potentially used in biomedical applications.